Effects of liquid water on transport in the catalyst layer of proton exchange membrane fuel cells - Min, Ting; Zhou, Qiang (Frontiers in Energy Research, 2023)
Catalyst layers (CLs) of proton exchange membrane fuel cells (PEMFCs) where the electrochemical reactions take place have a critical effect on the cell performance and liquid water forming in CLs during operation can influence the reactive transport processes which is challenge for experimental observation due to the temporal and spatial limitation. In this study, nanoscale structures of CLs in PEMFCs are reconstructed with pores, carbon, platinum (Pt) particles, and ionomers fully resolved. Distributions of liquid water with different saturations and wettabilities within nanoscale structures are simulated by the lattice Boltzmann method. Pore-scale modeling of oxygen reactive transport in the nanoscale structures is implemented, with oxygen diffusion in pores and ionomers, as well as an electrochemical reaction at the Pt surface considered. Effects of liquid water on the pore size distribution, electrochemical area, and oxygen concentration distribution are discussed. Liquid water in hydrophilic CL tends to form a film covering the reactive sites, while that in hydrophobic CL forms a droplet preferentially occupying large pores. For the hydrophilic case, local transport resistance increases significantly under a low saturation, while for the hydrophobic case, a remarkable increase in the local transport resistance can only be found after liquid water saturation higher than 0.8. Finally, the conjecture that liquid water in pores with a size smaller than a threshold pore size can conduct protons is considered. Different values of the threshold pore size are studied. The results show that when the threshold value is greater than 10 nm, the local transport resistance will decrease as the liquid water saturation increases, which means the optimizing strategy of CL needs to carefully consider the effects of liquid water.